RASIO CAMEL UNTUK MEMPREDIKSI KONDISI BERMASALAH PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Isworo, Sri Isworo (Jurnal Analisis Bisnis Ekonomi, 2010)
The purpose of this study is to analyze whether CAMEL ratios (CAR, ATTM, APB, NPL, P2AP, P3APAP, ROA, ROE, NIM, BOPO, LDR) can differentiate between financial distress and survive banks at Indonesian Stock Exchange over the 2001 2005 periods. The sample consisit of 10 banks which had 2 banks financial distess and 8 banks survive. The statistic method used to test research hypothesis are independent t test and regression logistic. With independent t test, the result shows that: 1) eight CAMEL ratios (APB, NPL, P2AP, P3APAP, ROA, ROE, NIM, BOPO, LDR) can differentiate between financial distress and survive banks 2) three CAMEL ratios (CAR, ATTM & P3AP ) cann not differentiate between financial distress and survive banks. With regression logistic stepwise method, the result shows that: three CAMEL ratios (ATTM, ROA & LDR) had classification power to predist financial distress and survive banks at Indonesian Stock Exchange.